Pemberdayaan Kelompok Rentan melalui Pelatihan Tata Kelola UMKM dalam Meningkatkan Kecakapan Hidup (Life Skills) di PKBM Panrita - Eli Eli; Ihwan Ridwan; Salmia Salama; Nursaidah Nursaidah (Prodi PGSD Unsultra, 2026)
The MSME governance training at the Panrita Community Learning Center (PKBM) aims to improve the life skills of vulnerable groups, including housewives, people with disabilities, and low-income communities, through participatory non-formal education. This activity includes participant identification, material planning, and a five-day training program with business simulations, case studies, group discussions, field practice, and mentoring. Evaluation was conducted through direct observation, pre- and post-test questionnaires, and reflective interviews. Results showed significant improvements in technical skills, such as financial record-keeping, business management, and marketing strategies, as well as soft skills, including communication, cooperation, negotiation, motivation, and self-confidence. Intensive interaction with mentors and hands-on practice helped participants overcome fear of failure, develop initiative, and build economic independence. Social impacts were also seen through increased community networking, collaboration, and solidarity among participants, which strengthened social capacity and business sustainability. These findings support previous research that emphasized the effectiveness of practice-based training and mentoring in the economic empowerment and life skills development of vulnerable groups. In conclusion, the MSME training at PKBM Panrita not only improves participants' technical and social competencies, but also fosters character, responsibility, discipline, and the ability to adapt to economic and social dynamics. This program serves as a sustainable community empowerment strategy relevant to local community needs.